Ardās of the Sikhs : A Distinctive Prayer - Neki, Jaswant Singh, (Brill | Manohar Publishers & Distributors, 2016)
This book, Ardās of the Sikhs , is an inclusive, yet discreet work on the subject. While acknowledging the universality of prayer and its efficacy, the author attends to this multisensate phenomenon in all its dimensions - historical, hermeneutical, psychological, philosophical etc. He does this with all deference to the various other extant spiritual disciplines. Ardās for the Sikhs is the way of life ordained by the Gurus. It is but another way of simran or Practising the Presence of God. It pithily condenses the cosmic glory, spiritual experiences and ethical values enshrined in the perennial holy Word of the Adi Granth. Profoundly expounding every phrase of the Ardās, the book has been considered a precious addition to the existing spiritual literature of the world. Its version in the Punjabi language had been described 'an all-time classic' by the Chief Editor of Encyclopaedia of Sikhism .